2021
DOI: 10.3390/en14165025
|View full text |Cite
|
Sign up to set email alerts
|

Induction Motor Direct Torque Control with Synchronous PWM

Abstract: A novel induction motor direct torque control (DTC) algorithm with synchronous modulation is presented. Compared to the traditional DTC method, whose main drawback is the presence of low-frequency torque harmonics (sub-harmonics), in the proposed method, the PWM switching frequency is imposed to be an integer multiple of the main supply frequency. This is achieved by continuously adjusting the PWM switching period to significantly reduce low-frequency harmonics. The devised algorithm has been tested on an inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The algorithms presented for estimation and compensation can be used also with other types of induction machine control, such as Direct Torque Control [15] and V/Hz control [16] to compensate for the cable effects. The major limitation of the compensation algorithm that resulted from this preliminary study was mainly due to the oscillations generated by the system composed by cable, filter, and motor and how the control algorithm of induction machines was affected by them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The algorithms presented for estimation and compensation can be used also with other types of induction machine control, such as Direct Torque Control [15] and V/Hz control [16] to compensate for the cable effects. The major limitation of the compensation algorithm that resulted from this preliminary study was mainly due to the oscillations generated by the system composed by cable, filter, and motor and how the control algorithm of induction machines was affected by them.…”
Section: Discussionmentioning
confidence: 99%
“…A speed estimation algorithm for an induction machine has already been discussed in [7], and it is shown in Figure 2. Measured stator currents and observed stator currents are compared using a vector product, as shown in Equation (15):…”
Section: Speed Estimation Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Cherifi et al [9] have proposed the Space Vector Modulation to reduce the oscillations observed in the created torque (SVM-DTC). Additionally, Y Benevieri et al [10] have suggested the synchronous DTC for reducing the harmonic spectrum content in the torque. The SMC has been proposed to control the DFI generator [11,12].…”
Section: Introductionmentioning
confidence: 99%